An fNIRS hyperscanning study on the influence of team type and sex on athletes’ interpersonal trust and neural mechanisms - Huiling Wang; Yisong Cong; Changjiang Liu; Lin Li (Scientific Reports)
Abstract Studies show that athletes have better trust behaviors than ordinary college students, likely due to their long-term sports training. However, the impact of sports training may vary with the team-based nature of the sports. It’s still unclear whether there are differences in interpersonal trust behaviors and neural mechanisms among athletes from different types of teams. This study compared the differences in these aspects between athletes from cooperative-competitive teams and those from competitive-cooperative teams. Our study recruited 48 athletes dyads. 24 dyads were from team sports (e.g., basketball, soccer) and were grouped into the cooperative-competitive group (cooperation group), since their training involved more cooperation than competition, including 12 male and 12 female dyads. The other 24 dyads, from individual sports (e.g., athletics, tennis), formed the competitive-cooperative group (competitive group), as their training was more competitive than cooperative, and also included 12 male and 12 female dyads. A two-factor experimental design was used. During trust-game tasks, interpersonal trust behaviors and prefrontal interpersonal neural synchronization (INS) changes were monitored in real time via functional Near-infrared Spectroscopy (fNIRS) hyperscanning. Behaviorally, the cooperation group showed more investment behaviors in trust games than the competition group. In brain data, during investment decisions, female athletes in the cooperation group had stronger left frontal lobe INS than those in the competition group. Also, in the competition group, female athletes showed stronger left dorsolateral prefrontal INS during investment decisions than male athletes. The study indicates that team type and sex significantly affect athletes’ interpersonal trust behaviors, along with specific brain area INS changes. It offers a new angle for research on sports training and trust behavior, filling a gap in the field.